2007
DOI: 10.1080/02652030601101110
|View full text |Cite
|
Sign up to set email alerts
|

Screening of fermentative bacteria for their ability to bind and biotransform deoxynivalenol, zearalenone and fumonisins in anin vitrosimulated corn silage model

Abstract: Fermentative bacteria can potentially be utilized to detoxify corn silage contaminated by Fusarium toxins. The objective of the present study was to test a large number of these bacteria for their ability to bind and/or biotransform deoxynivalenol (DON), zearalenone (ZEN) and fumonisins B(1) and B(2) (FB(1), FB(2)) in conditions simulating corn silage. A total of 202 strains were screened in contaminated, pH 4, corn infusion inoculated with 5 x 10(8) CFU ml(-1). Eight Lactobacilli and three Leuconostoc biotran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
75
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(85 citation statements)
references
References 32 publications
6
75
0
4
Order By: Relevance
“…Various studies have clearly demonstrated that diverse microorganisms could act as natural antagonists of plant pathogens. Among these microorganisms, lactic acid bacteria that have a long history of use in food and feed and are generally considered as safe organisms have been reported to effectively reduce mould growth and to interact with mycotoxins (El-Nezami, Polychronaki, Salminen, & Mykkanen, 2002;Niderkorn et al, 2006Niderkorn et al, , 2007Niderkorn et al, , 2009). However, little is known regarding the impact of these microorganisms on mycotoxin production and especially Fusarium toxins.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have clearly demonstrated that diverse microorganisms could act as natural antagonists of plant pathogens. Among these microorganisms, lactic acid bacteria that have a long history of use in food and feed and are generally considered as safe organisms have been reported to effectively reduce mould growth and to interact with mycotoxins (El-Nezami, Polychronaki, Salminen, & Mykkanen, 2002;Niderkorn et al, 2006Niderkorn et al, , 2007Niderkorn et al, , 2009). However, little is known regarding the impact of these microorganisms on mycotoxin production and especially Fusarium toxins.…”
Section: Discussionmentioning
confidence: 99%
“…Becker et al (1997) reported that FB 1 was not degraded by Enterococcus faecium while the binding of FB 1 and FB 2 , up to 24 and 62%, respectively by Enterococcus sp. was determined (Niderkorn et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The ability to bind and/or biotransform the mycotoxins typical for maize silage was tested in 202 bacterial strains (Niderkorn, Morgavi, Pujos, Tissandier, & Boudra, 2007). Several Lactobacillus and Leuconostoc species biotransformed zearalenone into a-zearalenol, but deoxynivalenol and fumonisins B 1 and B 2 were not transformed.…”
Section: Mycotoxinsmentioning
confidence: 99%